Farmers and Agricultural Extension Officers Perception of Striga gesnerioides (Willd.) Vatke Parasitism on Cowpea in the Upper East Region of Ghana. (5th August 2018) - Haruna, Peter; Asare, Aaron T.; Asare-Bediako, Elvis; Kusi, Francis
Abstract : Cowpea [ Vigna unguiculata (L.) Walp] is an important food security crop in Sub-Saharan Africa. However, cowpea production in some parts of this region is constrained by Striga gesnerioides (Willd.) Vatke infestation resulting in yield losses. This study assessed the farmers and agricultural extension officers (AEOs) perception of S. gesnerioides parasitism on cowpea in the Upper East Region of Ghana. In all, 200 respondents—179 cowpea farmers and 21 AEOs—in five cowpea growing districts were randomly sampled to answer closed- and opened-ended questions coupled with visit to cowpea farms. Majority of the farmer respondents were males between the ages of 21 and 60 with very little or no formal education. Almost all of the respondents could identify the parasitic weed, S. gesnerioides, but they lacked adequate knowledge of the parasitic effects on the host, cowpea plant. S. gesnerioides infestation was widespread and devastating in almost all the fields surveyed. Its effects on the host plants (cowpea) included stunted growth, leaf senescence, chlorosis, death of the crop, and reduced yield. Different management strategies employed by the farmers to contain the spread of the parasite include weeding (90%), application of manure (5.5%), and crop rotation and fallowing (4.0%). Both farmers and extension officers had very little knowledge on existence of S. gesnerioides resistant cowpea genotypes for cultivation. Farmers expressed the desire to cultivate Striga -resistant cowpea varieties when made accessible, since it is the most reliable and environmentally friendly method of controlling the parasitic weed.